Cambridge East Greenland expedition 1971, preliminary report - Billinghurst, Anthony W.; Karney, Charles F. F.; Squibbs, R. F.; Williams, S. T. (Zenodo, 1971)
The principal aim of the Expedition was to continue and complete certain aspects of the detailed glaciological survey of the Roslin glacier carried out by the Cambridge Staunings Expedition of 1970, namely: To locate and re-establish the August 1970 stake patterns on the upper Roslin glacier, and to fix their new positions by theodolite triangulation. To map by plane table the lower 2 kilometres of the Roslin glacier. To measure the conductivity of the ice melt water at various points on the Roslin glacier.